From international competition to intercultural competence: Considerations on the use of practice mobility as an internationalisation strategy in Norwegian teacher education - Sjøen, Martin M. (Nordic Journal of Comparative and International Education (NJCIE), 2023)
This study explores international practicums in Norwegian teacher education. The study is based on a qualitative survey of teacher education institutions in combination with discourse analysis of the white paper on the internationalisation of education (Meld. St. 7 (2020—2021)). The aim is to contribute towards synthesising knowledge on the use of international practicums as an internationalisation strategy in Norway. The survey finds that international practicums are widely used, yet variations in content, form and implementation exist between different institutions. This is explained by how international practicums are neither regarded, nor rewarded as a formal internationalisation strategy in Norway. Analysis of the white paper reveals tensions between different educational discourses on internationalisation. While the discourse analysis identifies political recognition of international practicums in teacher education, the Norwegian Government remain reluctant to recognise international practicums as a formalised internationalisation strategy. The study concludes that this prioritisation risks undermining parts of the fundamental purpose of internationalisation, which is understood as the integration of international, intercultural and global dimensions throughout the educational system.